Ленинская теория империализма и современность - Иноземцев Николай Николаевич (Мысль, 1977)
Экземпляры: КХ (20231024) / Инвентарный номер: 665390 / Сис.шифр: 33-2 / Авт.знак: Л 45 / ГРНТИ: 11 / ББК: 65